2021
DOI: 10.1002/hep.31848
|View full text |Cite
|
Sign up to set email alerts
|

Perivenous Stellate Cells Are the Main Source of Myofibroblasts and Cancer‐Associated Fibroblasts Formed After Chronic Liver Injuries

Abstract: BaCKgRoUND aND aIMS: Studies of the identity and pathophysiology of fibrogenic HSCs have been hampered by a lack of genetic tools that permit specific and inducible fate-mapping of these cells in vivo. Here, by single-cell RNA sequencing of nonparenchymal cells from mouse liver, we identified transcription factor 21 (Tcf21) as a unique marker that restricted its expression to quiescent HSCs. appRoaCH aND ReSUltS: Tracing Tcf21 + cells by Tcf21-CreER (Cre-Estrogen Receptor fusion protein under the control of Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The liver TME is composed of liver resident cells such as liver sinusoidal endothelial cells, HSCs, and Kupffer cells [35] and of other cell types such as myeloid-derived suppressor cells, regulatory T-cells, tumour-associated macrophages, and cancer-associated fibroblasts (CAFs) [39,40]. Recent studies have shown that HSCs are the major source of CAFs in liver cancer, although a small portion of the CAFs can be derived from other cell types, as shown in Figure 1 [9,41]. In conclusion, CAFs appear to be involved in every step of liver cancer development.…”
Section: Role Of Microenvironment In Liver Tumour Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver TME is composed of liver resident cells such as liver sinusoidal endothelial cells, HSCs, and Kupffer cells [35] and of other cell types such as myeloid-derived suppressor cells, regulatory T-cells, tumour-associated macrophages, and cancer-associated fibroblasts (CAFs) [39,40]. Recent studies have shown that HSCs are the major source of CAFs in liver cancer, although a small portion of the CAFs can be derived from other cell types, as shown in Figure 1 [9,41]. In conclusion, CAFs appear to be involved in every step of liver cancer development.…”
Section: Role Of Microenvironment In Liver Tumour Developmentmentioning
confidence: 99%
“…However, the definition by Sahai et al does not allow distinguishing CAFs from common myofibroblasts including non-tumour-associated activated HSCs. In the liver, activated HSCs (aHSCs) are the main myofibroblast source upon injury and fibrogenesis [ 41 , 67 ]. These aHSCs express PDGF-bb, TGF-β, IL-6 and IL-1b.…”
Section: Definition and Use Of Cafs For In Vitro Liver Cancer Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, hepatic stellate cells (HSCs) are arguably the major source of ECM and play a central role in liver fibrogenesis (7)(8)(9). Mechanistically, several key pathways drive HSC activation, except for transforming growth factor-beta (TGF-β) signaling and phosphatidylinositol 3-kinase/ protein kinase B (PI3K/AKT) signaling (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…Meng’s results (13) suggested that NLRP3 inflammasome activation in HSCs might serve as an early mechanism to turn on the inflammatory response and thereby induce liver fibrosis during Schistosoma infection. Cai et al (14) demonstrated that Angiotensin -(1-7) (Ang-(1-7)) improved liver fibrosis by regulating NLRP3 inflammasome activation induced by Ang II-mediated reactive oxygen species (ROS) production via redox balance modulation.…”
Section: Introductionmentioning
confidence: 99%